2016
DOI: 10.1155/2016/8380618
|View full text |Cite
|
Sign up to set email alerts
|

Deposition of BACE-1 Protein in the Brains of APP/PS1 Double Transgenic Mice

Abstract: The main causes of Alzheimer's disease remain elusive. Previous data have implicated the BACE-1 protein as a central player in the pathogenesis of Alzheimer's disease. However, many inhibitors of BACE-1 have failed during preclinical and clinical trials for AD treatment. Therefore, uncovering the exact role of BACE-1 in AD may have significant impact on the future development of therapeutic agents. Three- and six-month-old female APP/PS1 double transgenic mice were used to study abnormal accumulation of BACE-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Figure 3A presents images of Aβ-plaque immunoreactivity in the hippocampus and cortex of the 4 groups, showing that 2 × Tg-AD mice at 10 months of age developed obvious Aβ-plaque deposition in both hippocampus and cortex. This AD-like pathogenesis was consistent with previous reports (Capell et al, 2000;Luo et al, 2016). Compared with vehicle-treated Non-Tg mice, quantitative analysis revealed that the vehicle-treated 2 × Tg-AD mice exhibited a significantly greater Aβ-plaque load in the hippocampus (Figure 3B, P < 0.001) and cortex ( Figure 3C, P < 0.001).…”
Section: Ech Reduces Cerebral Aβ-positive Plaque Load and Aβ Productisupporting
confidence: 91%
“…Figure 3A presents images of Aβ-plaque immunoreactivity in the hippocampus and cortex of the 4 groups, showing that 2 × Tg-AD mice at 10 months of age developed obvious Aβ-plaque deposition in both hippocampus and cortex. This AD-like pathogenesis was consistent with previous reports (Capell et al, 2000;Luo et al, 2016). Compared with vehicle-treated Non-Tg mice, quantitative analysis revealed that the vehicle-treated 2 × Tg-AD mice exhibited a significantly greater Aβ-plaque load in the hippocampus (Figure 3B, P < 0.001) and cortex ( Figure 3C, P < 0.001).…”
Section: Ech Reduces Cerebral Aβ-positive Plaque Load and Aβ Productisupporting
confidence: 91%
“…As a progressive condition of neurodegeneration featuring cognitive impairment, behavioral abnormalities, and neuropsychiatric indications [ 1 , 2 ], Alzheimer’s disease (AD) is the chief pathogenic factor of dementia, which has become one of the greatest burdens of the century. Currently, the number of people having AD is over 50 million worldwide and, by 2050, the number is estimated to become 100 million.…”
Section: Introductionmentioning
confidence: 99%
“…Demars et al measured high APP protein levels in 2-month-old APP/PS1 animals [ 26 ], which agrees with our findings. Previous studies have shown that both the BACE1 protein level [ 80 ] and the enzymatic activity are elevated [ 81 ], and BACE1 is accumulated around plaques in AD models, independent of age [ 80 , 82 , 83 ]. We assume that changes in the amounts of products formed in the amyloidogenic pathway may support the hypothesis that the enhanced expression and/or activity of BACE1 is likely to contribute to the cleavage of APP, resulting in reduced APP and elevated C99 levels in Tg animals.…”
Section: Discussionmentioning
confidence: 99%